Renal Parameters in Mild, Moderate, and Chronic Cigarette Smokers - Dinesh Kumar; Preeti Sharma; Sudeep Kumar; Sumesh Prasad Sah; Manisha Arora; Shahid Iqbal; Pradeep Kumar (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To explore the link between cigarette smoking and kidney function through renal parameter assessment.Methods: The present study was performed at the Department of Biochemistry Santosh Medical College, Ghaziabad, India, from September 2019 to April 2021. In this study, 140 subjects were included, out of which 35 were non-smokers, 35 smoked <5 cigarette per day, 35 smoked 5-10 cigarette per day, and the remaining 35 smoked more than 10 cigarettes per day.Results: Blood urea, serum creatinine, urinary albumin, and uACR levels were found to increase significantly (p<0.001) in smokers as compared to non-smokers. These increases were higher among chronic cigarette smokers (p<0.001) as opposed to mild and moderate smokers. In contrast, serum uric acid, e-GFR, and urinary creatinine levels decreased significantly (p<0.001) in smokers when compared to non-smokers, with a higher decrease observed in chronic cigarette smokers (p<0.001) as opposed to the mild and moderate cigarette smokers.Conclusion: Alterations in urinary albumin, serum urea, serum creatinine, urinary creatinine, and e-GFR are associated with the risk of renal dysfunction.